1992
DOI: 10.1021/tx00029a003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and sequence-specific DNA binding of a topoisomerase inhibitory analog of Hoechst 33258 designed for altered base and sequence recognition

Abstract: The preparation and DNA binding characteristics of a structural analog of Hoechst 33258 bearing two pyridinic nitrogen atoms are described. The 1H NMR signals of the complex formed between the new ligand 1 and decadeoxyribonucleotide d(CATGGCCATG)2 were assigned by employing one- and two-dimensional NMR techniques. Intermolecular nuclear Overhauser effects (NOE) between the ligand and the DNA receptor fragment confirm that the ligand binds in the minor groove of the DNA, interacting with the centrally located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(54 citation statements)
references
References 45 publications
0
54
0
Order By: Relevance
“…41 An analog of Hoechst 33258, bearing a phenolic hydroxyl group in the meta rather than para position, was considerably less cytotoxic than the para one 42 and this difference may reflect cell permeation or ligand access to the nucleus once internalized. The structural modification that were employed included the replacement of one of both benzoimidazole rings with benzoxazoles 43 and pyridoimidazole, 43,44 the introduction of an N 1 -alkoxyalkyl moiety 45 and the alkylation of the terminal phenoxy moiety. 46,47 These modifications produced an enhanced cytotoxic potency with respect to parent compound Hoechst 33258.…”
Section: B I S -B E N Z I M I D a Z O L E Smentioning
confidence: 99%
See 1 more Smart Citation
“…41 An analog of Hoechst 33258, bearing a phenolic hydroxyl group in the meta rather than para position, was considerably less cytotoxic than the para one 42 and this difference may reflect cell permeation or ligand access to the nucleus once internalized. The structural modification that were employed included the replacement of one of both benzoimidazole rings with benzoxazoles 43 and pyridoimidazole, 43,44 the introduction of an N 1 -alkoxyalkyl moiety 45 and the alkylation of the terminal phenoxy moiety. 46,47 These modifications produced an enhanced cytotoxic potency with respect to parent compound Hoechst 33258.…”
Section: B I S -B E N Z I M I D a Z O L E Smentioning
confidence: 99%
“…Furthermore, this substitution could confer to the dimer or trimer agents' different properties in in vivo studies. Some examples of heteroaryl derivatives of CPI are depicted (compounds [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Each of these compounds showed different degrees of cytotoxicity and they have been used to obtain new pharmacological tools but, most importantly, they can represent possible probes for investigating the bioorganic properties of this exceptionally potent class of derivatives.…”
Section: E C T E I N a S C I D I Nmentioning
confidence: 99%
“…It is significant not only in understanding the mechanism of interaction, but also for guiding the design of new drugs. So it is necessary to understand the modes and the factors affecting the binding of small molecules to DNA (Singh et al, 1992). Studying the binding mechanism is of great importance in terms of life science, chemicals, pharmaceuticals, and clinical medicines (Bera et al, 2008;Zhao et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This finding has stimulated the research in finding new antitumour drugs containing planar fused ring system. In recent years various fused systems such as thiophene, 15 furan and pyridine analogues of ellipticine 16 and benzothiazoloquinolines 17 have been studied for their properties. Recently, Cao and He 15 studied DNA affinity properties of safranine-T which features a planar phenazine ring and have shown that electrostatic binding plays an important role in the intercalation of safranine-T.…”
Section: Introductionmentioning
confidence: 99%